2022
DOI: 10.1111/eva.13345
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and testing marker–trait associations for growth and phenology in three pine species: Implications for genomic prediction

Abstract: In tree species, genomic prediction offers the potential to forecast mature trait values in early growth stages, if robust marker–trait associations can be identified. Here we apply a novel multispecies approach using genotypes from a new genotyping array, based on 20,795 single nucleotide polymorphisms (SNPs) from three closely related pine species (Pinus sylvestris, Pinus uncinata and Pinus mugo), to test for associations with growth and phenology data from a common garden study. Predictive models constructe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 100 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…This close genetic similarity between the species is usually explained by relatively recent speciation in presence of gene flow (Christensen, 1987;Monteleone et al, 2006;Jasińska et al, 2010) and segregation of ancestral variation (Wachowiak et al, 2011(Wachowiak et al, , 2013. Comparative transcriptome analysis of these pines (Wachowiak et al, 2015) revealed thousands of polymorphic markers that were used for the development of SNP genotyping array (Perry et al, 2020), which has since been used to identify loci significantly associated with key adaptive traits, including growth and phenology (Perry et al, 2022). Genomic studies support the phylogenetically close relationship between two mountain pine taxa as compared to Scots pine and reveal some candidate regions under selection during the species evolution (Zaborowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This close genetic similarity between the species is usually explained by relatively recent speciation in presence of gene flow (Christensen, 1987;Monteleone et al, 2006;Jasińska et al, 2010) and segregation of ancestral variation (Wachowiak et al, 2011(Wachowiak et al, , 2013. Comparative transcriptome analysis of these pines (Wachowiak et al, 2015) revealed thousands of polymorphic markers that were used for the development of SNP genotyping array (Perry et al, 2020), which has since been used to identify loci significantly associated with key adaptive traits, including growth and phenology (Perry et al, 2022). Genomic studies support the phylogenetically close relationship between two mountain pine taxa as compared to Scots pine and reveal some candidate regions under selection during the species evolution (Zaborowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%